2017
DOI: 10.3311/ppme.9013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Transverse Vibration Acceleration of a High-Speed Elevator with Random Parameters under Random Excitation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Moreover, mathematical models to represent high rise elevators (Crespo et al, 2018;Fortgang et al, 2006), and specific parts of the elevator system such as the ropes (Kaczmarczyk et al, 2003) and the compensating sheave (Watanabe and Okawa, 2018) are found. The cabin has also been extensively studied because it is vulnerable to the vertical and the lateral vibrations that affect the passenger comfort (Coffen et al, 1997;Feng et al, 2009;Herrera et al, 2010Herrera et al, , 2014aQiu et al, 2020;Zhang and Yang, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mathematical models to represent high rise elevators (Crespo et al, 2018;Fortgang et al, 2006), and specific parts of the elevator system such as the ropes (Kaczmarczyk et al, 2003) and the compensating sheave (Watanabe and Okawa, 2018) are found. The cabin has also been extensively studied because it is vulnerable to the vertical and the lateral vibrations that affect the passenger comfort (Coffen et al, 1997;Feng et al, 2009;Herrera et al, 2010Herrera et al, , 2014aQiu et al, 2020;Zhang and Yang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of both internal and external variables on the dynamics of the elevator system has also been assessed. Regarding the internal variables, the influence of the design parameters of the elevator (Qiu et al, 2020; Vladić et al, 2011) and the influence of random parameters caused by manufacturing and installation errors (Zhang and Yang, 2017) are studied optimizing the elevator system. In addition, external variables may also influence the behavior of the system.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of operation, the car is influenced by a lot of uncertainties, such as irregularity excitation of guide rail, 1114 airflow excitation, 15,16 rope swing excitation, 1720 and so on, and all the uncertainties can be combined into, over centroid O , an X -direction excitation Fx, Y -direction excitation Fy, θx-direction excitation Fy, θy - direction excitation T y , and θz-direction excitation TZ. The control force of the actuator in the direction of X is Fcx and Y -direction is Fcy.…”
Section: Introductionmentioning
confidence: 99%